Business model innovation processes in large corporations: insights from BASF. Issue 2 (18th April 2017) - Winterhalter, Stephan; Weiblen, Tobias; Wecht, Christoph H.; Gassmann, Oliver
Abstract : Purpose: Despite the fact that business model innovation (BMI) has attracted intense attention from scholars and practitioners alike, practicable knowledge on the organizational implementation of BMI efforts in large multinational corporations is rather rare. This paper aims to investigate how BMI is managed in the complex environment of the chemical industry based on a study at BASF SE, a leading global chemical company. Design/methodology/approach: The empirical data draw from six case studies (i.e. six BMI projects) within BASF which were observed in the 2010-2014 timeframe. Findings: There is not one uniform BMI process archetype. Three different types can be identified, whereby the degree of technology involvement and the maturity of this technology act as determining factors for the form of the process and its organizational implementation. Originality/value: This paper profits from its unique empirical setting, which allows identifying practices for the organizational implementation of systematic BMI processes in large corporations. The guidelines derived are highly relevant for general managers and business development departments.